Malaria and pregnancy: evaluation of the strategies in malaria control during the antenatal clinics in the South of Cameroon - (:unkn) unknown (My University, 2005)
Summary: Objective: To carry out an assessment of the strategies in malaria control during pregnancy in a rubber plantation of the south of Cameroon. Methods: Cross-sectional study with a questionnaire on the ANC’s process and the malaria perception with mothers of children of less than six months. Results: The malaria prevention was accepted by 62% of the women coming in antenatal clinics and used mainly AQ (36%), CQ (37%) in only one cure, both (16%) or Q (10%). Malaria illness occurred for 32% of the women who had received a preventive treatment and for 52% of the women who had not had it: AQ or Q were the first line treatments. 47% of the women confirmed having received information about treatments and 52% information about malaria. Conclusion: The availability of antimalarial drugs in the care structures as well as training and updating for health personnel are essential for the achievement of the objectives of malaria control programme. Moreover, the contents of the informational messages on malaria intended for the pregnant women should take into account their representations of the disease.
Keywords: African Research